IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS MODERASI BERAGAMA DISEKOLAH SMP 2 BENGKALIS - Dani, Ramah; Rahmayani, Ridha; Nuramini, Aisyah (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
Indonesia has a unique diversity where there are various kinds of ethnicity, language, race, nation and religion. Religious moderation has several opinions according to experts and. Viewed from the opinion according to Abdurahman Mas'ud, this moderation can mean placing a balance above faith, morals and morals, both viewing other people as individuals, as well as above state institutions. Moderation of religion within the framework of Islam is reflected in all aspects of Islamic teachings themselves. Tolerance is mutual respect for one another to present a community that must be managed. The research method used in this study is a qualitative research method, which uses a particular type of field research (Field Research). Qualitative research methods serve to obtain in-depth information and capture the intent of the field